2009
DOI: 10.1007/s11101-009-9125-9
|View full text |Cite
|
Sign up to set email alerts
|

Recent developments in the rapid analysis of plants and tracking their bioactive constituents

Abstract: Natural products chemistry has witnessed many new developments in the last 5 years like extractions with subcritical water and ionic liquids,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 46 publications
1
28
0
Order By: Relevance
“…It has been demonstrated that combination of high-end analytical technologies facilitates the structure elucidation process of small mass molecules present in minute quantities in valuable samples. In this respect, several applications have been recently developed, such as LC-SPE-NMR or the more efficient LC-SPE-NMR-MS set up which overcomes the limitation of direct coupling between LC and NMR (Schlotterbeck & Ceccarelli, 2009;Yang et al, 2009;Van Beek et al, 2009). The instrumental setup of these techniques implies the physical joint of chromatographic-based instruments to spectroscopic detection-based instrumentations, making these systems not easily affordable to standard research laboratories.…”
Section: Analytical Techniquesmentioning
confidence: 99%
“…It has been demonstrated that combination of high-end analytical technologies facilitates the structure elucidation process of small mass molecules present in minute quantities in valuable samples. In this respect, several applications have been recently developed, such as LC-SPE-NMR or the more efficient LC-SPE-NMR-MS set up which overcomes the limitation of direct coupling between LC and NMR (Schlotterbeck & Ceccarelli, 2009;Yang et al, 2009;Van Beek et al, 2009). The instrumental setup of these techniques implies the physical joint of chromatographic-based instruments to spectroscopic detection-based instrumentations, making these systems not easily affordable to standard research laboratories.…”
Section: Analytical Techniquesmentioning
confidence: 99%
“…The UHPLC offers two interesting possibilities: either very fast separation (1 min) using short columns at high flow or ultra high resolution [115]. Thus, UHPLC makes it possible to perform higher solution separations superior to HPLC analysis by using solid phase particles of less than 2 mm in diameter to achieve superior sensitivity and resolution.…”
Section: Uhplcmentioning
confidence: 99%
“…The technical changes constist of a larger column oven, a preheater for the mobile phase before the column and a cooler for the mobile phase after the column. One study showed that the retention time with methanol-water [10:90 (v/v)] decreased from 24 to 2 min when the temperature was increased from 90 to 205 °C [115,116] .…”
Section: High Temperature Hplcmentioning
confidence: 99%
“…Such approaches are often referred to as high-resolution screening. [21] An example is the development of HPLC on-line assays to test for antioxidant activity, which is of interest for nutraceuticals. This type of product often has health claims related to antioxidant properties since many chronic diseases (e.g.…”
Section: Profiling Phytonutrients In Nutraceuticalsmentioning
confidence: 99%
“…When combined with LC-MS and LC-NMR, reliable identification of active constituents becomes possible without the need of ever isolating them in a classical sense. [21] Enzyme assays are, however, often not compatible with HPLC because of the organic modifier concentrations commonly used. Furthermore, the reaction time is often long and requires lengthy coils.…”
Section: Profiling Phytonutrients In Nutraceuticalsmentioning
confidence: 99%